Coaching for accelerated research productivity in Higher Education - Geber, Hilary (The International Journal of Evidence Based Coaching and Mentoring Oxford Brookes University, 2010)
It is recognized that combining a thorough orientation to academic life and its expectations with intensive training in conceptualising research can accelerate the careers of early career academics. Unique to the structured support programme for research productivity and publication at the University of the Witwatersrand, Johannesburg, was ongoing internal coaching of participants. In the study reported here in-depth interviews of participants and coaches were used to collect data. Internal coaches are academics without being experts in the participants’ disciplines. Goal alignment linked to both individual and organisational objectives resulted in tangible outcomes for research, publication and career changes. Less tangible outcomes concern the value of coaching; coaching during career or personal critical incidents and the important shifts in thinking which occurred. The outcomes have drawn additional funding to the University, and there is ongoing wider implementation across faculties of the programme with internal coaching.
Keywords: internal coaching; early career academics; structured support; research productivity; publication